Changes in Angular Size and Speed Affect the Judged Height of Objects Moving over a Ground Surface. (January 2013) - Zhang, Junjun; Braunstein, Myron L; Andersen, George J
Kersten et al (1997, Perception 26 171–192) showed that the perceived path of an object moving over a ground surface can be manipulated by changing the path of a shadow. Using a scene similar to Kersten's "ball-in-a-box" scene, we investigated the effect of angular size and angular speed in determining the perceived height of a moving sphere when optical contact (the position at which the object contacted the ground in the image) indicated that the sphere was receding in depth. In four experiments we examined both the effects of changes in size and speed, and the effects of constant levels of size and speed. Increases in angular size or speed during a motion sequence resulted in judgments of increased height above the ground plane. The angular size at the end of the motion sequence was also important in determining judged height, with greater height judged with larger final sizes.